Methods from information extraction from LiDAR intensity data and multispectral LiDAR technology - Scaioni, Marco; Höfle, Bernhard; Baungarten Kersting, Ana P.; Barazzetti, Luigi; Previtali, Mattia; Wujanz, Daniel (ISPRS TC III Mid-term Symposium "Developments, Technologies and Applications in Remote Sensing", 2018)
LiDAR is a consolidated technology for topographic mapping and 3D reconstruction, which is implemented in several platforms On the other hand, the exploitation of the geometric information has been coupled by the use of laser intensity, which may provide additional data for multiple purposes. This option has been emphasized by the availability of sensors working on different wavelength, thus able to provide additional information for classification of surfaces and objects. Several applications ofmonochromatic and multi-spectral LiDAR data have been already developed in different fields: geosciences, agriculture, forestry, building and cultural heritage. The use of intensity data to extract measures of point cloud quality has been also developed. The paper would like to give an overview on the state-of-the-art of these techniques, and to present the modern technologies for the acquisition of multispectral LiDAR data. In addition, the ISPRS WG III/5 on ‘Information Extraction from LiDAR Intensity Data’ has collected and made available a few open data sets to support scholars to do research on this field. This service is presented and data sets delivered so far as are described.
Gesehen am 29.07.2024